Improving the Awareness of Musculoskeletal Disorder Risks Among Dental Educators. Issue 1 (24th January 2020) - Partido, Brian B.; Henderson, Rebecca P.; Kennedy, Meredith
Abstract: Prolonged and static postures among dental workforce personnel may lead to work‐related musculoskeletal disorders (WMSDs). The aim of this study was to determine whether feedback involving photography and self‐assessment would improve dental educators' postures and accuracy of ergonomic self‐assessment. This study used a randomized control design. The Modified‐Dental Operator Posture Assessment Instrument (M‐DOPAI) was used for all ergonomic evaluations over a four‐week period at one U.S. dental school. At week 1, all 30 participating dental educators were photographed and completed an M‐DOPAI without viewing the photographs. In weeks 2 and 3, the educators in the control group (N=15) completed an M‐DOPAI without any additional photographs. The educators in the training group (N=15) had additional photographs taken and used the photographs to complete an ergonomic self‐assessment with the principal investigator. From week 1 to week 4, the ergonomics training utilizing photography resulted in improvements in the dental educators' ergonomic scores but not the accuracy of their ergonomic self‐assessments. All participants strongly agreed it was important for both dental students and dentists to understand proper ergonomics, properly apply proper ergonomics, and have accurate ergonomic self‐assessment skills in clinical practice. Although these dental educators valued ergonomic principles, they lacked training in applying these principles with dental students. Without additional training in ergonomics and self‐assessment, the development of these skills in dental students will be affected.